A Re-assessment of Minocycline as a Neuroprotective Agent in a Rat Spinal Cord Contusion Model - Pinzon, Alberto (2008)
This study was initiated due to an NIH “Facilities of Research-Spinal Cord Injury” contract to support independent replication of published studies that could be considered for a clinical trial in time. Minocycline has been shown to have neuroprotective effects in models of central nervous system injury, including in a contusive spinal cord injury (SCI) model at the thoracic level. Beneficial effects of minocycline treatment included a significant improvement in locomotor behavior and reduced histopathological changes (Lee et al., 2003) To verify these important observations, we repeated this study in our laboratory. The NYU (MASCIS) Impactor was used to produce a moderate cord lesion at the vertebral level T9–T10 (height 12.5 mm, weight 10 g), (n=45), followed by administration of minocycline, 90mg/kg (group 1: minocycline IP, n=15; group 2: minocycline IV, n=15; group 3: vehicle IP, n=8; group 4: vehicle IV, n=7) immediately after surgery and followed by two more doses of 45 mg/kg/IP at 12 hrs and 24 hrs. Open field locomotion (BBB) and subscores were examined up to 6 weeks after SCI and cords were processed for quantitative histopathological analysis. Administration of minocycline after SCI did not lead to significant behavioral or histopathological improvement. Although positive effects with minocycline have been reported in several animal models of injury with different drug administration schemes, the use of minocycline following contusive SCI requires further investigation before clinical trials are implemented.